Comparative analysis of mitochondrial genomes of Broussonetia spp. (Moraceae) reveals heterogeneity in structure, synteny, intercellular gene transfer, and RNA editing - Lai, Chanjuan; Wang, Jie; Kan, Shenglong; Zhang, Shuo; Li, Pan; Reeve, Wayne Gerald; Wu, Zhiqiang; Zhang, Yonghua (Frontiers in Plant Science, 2022)
Broussonetia (Moraceae) comprises three recognized species that are essential in the development of papermaking and barkcloth-making technology around the world, and they also work as medicine in several countries. Despite their important economical, medicinal, and ecological values, the complete mitogenome of Broussonetia has not been reported and investigated, which has greatly inhibited the research on molecular evolution and production. Here, we assembled the first-reported three complete Broussonetia (B. papyrifera, B. kaempferi, and B. monoica) mitochondrial genomes (mitogenome) based on a hybrid strategy using Illumina and Oxford Nanopore sequencing data, and performed comprehensive comparisons in terms of their structure, gene content, synteny, intercellular gene transfer, phylogeny, and RNA editing. Our results showed their huge heterogeneities among the three species. Despite that B. monoica and B. papyrifera showed a single circular structure, the B. kaempferi mitogenome was unique to have a double circular structure. Gene content was consistent except for a few transfer RNA (tRNA) genes. Synteny among Broussonetia spp. illustrated high conservativeness in sequences, and that B. monoica with B. kaempferi was closer to each other with more synteny blocks, which was well-supported in organellar phylogeny. Detection of the transfer fragments between organellar genomes demonstrated that they were derived from some hotspots across plastome and had been integrated under potential mediation of tRNA genes in mitogenome. In addition, RNA editing sites showed great differences in abundance, type, location, and efficiency among species and tissues. Conclusively, the complete gap-free mitogenomes of Broussonetia spp. would provide massive genetic resources for evolutionary research and communications between the two organelle genomes.